A Summary of the Seventh Annual Review of the BCPC's Pests and Beneficials Group. (1st October 2022) - Blake, Robin
The purpose of the Pests and Beneficials Group is to provide a forum for discussion of relevant research results and new legislation and impact on integrated pest management. The objective of this meeting was to understand better how to deliver practical IPM solutions to farmers. This starts with the policy context, followed by research that can be done and finally the delivery of tools and information to famers and the successful implementation of IPM in the field. The meeting also sought to highlight the need to integrate the thinking about the implications of combining IPM management decisions for insect, disease and weed pests and the trade-offs that may have to be made as a result. Cathryn Lambourne, Knowledge Transfer Manager from Agrifood section of the KTN (Knowledge Transfer Network), UKRI provided an account of the work of the KTN, particularly in the Agrifood sector, providing support for those seeking information, funding, and connections within the industry followed by a short outline of the principles of IPM.